A Novel Blockchain-Based Approach for Secure and Efficient Database Management - Chandan Kalita (International Journal of Intelligent Systems and Applications in Engineering, 2024)
This paper introduces a novel blockchain-based approach for secure and efficient database management. Blockchain technology, with its decentralized, immutable, and transparent nature, offers significant advantages over traditional database systems, particularly in enhancing data security, integrity, and auditability. The proposed approach leverages blockchain’s cryptographic mechanisms and consensus algorithms to create a robust framework for managing sensitive data. By decentralizing data storage and ensuring that all transactions are recorded in a tamper-evident manner, this method addresses critical vulnerabilities present in conventional databases. Additionally, the approach aims to improve operational efficiency by reducing reliance on intermediaries and streamlining verification processes. The paper also discusses the challenges associated with blockchain implementation, such as scalability, regulatory compliance, and integration with existing systems, and proposes potential solutions to mitigate these issues. Through comprehensive analysis and experimentation, the study demonstrates the feasibility and benefits of integrating blockchain technology into modern database management systems, paving the way for more secure, transparent, and efficient data handling practices. This novel blockchain approach integrates data compression and encryption to enhance performance, security, and efficiency. Transactions are compressed to reduce size and encrypted to ensure data security before being added to the blockchain. During retrieval, data is decrypted and decompressed for verification and use, optimizing resource usage while maintaining integrity and confidentiality.